Linguopoetic Features Of Some Examples Of The Art Of Simile In The Tragedy “Mirzo Ulugbek” - Ikramova Muhtaram (International Journal Of Literature And Languages, 2025)
The article presents a semantic, functional, and stylistic analysis of certain similes in Maqsud Shayxzoda’s tragedy “Mirzo Ulugbek”.